Insolvency administrator's incentives and the tradeoff between creditor satisfaction and efficiency in bankruptcy procedures - Matthias Frieden; Stefan Wielenberg (Business Research, 2017)
An insolvency administrator replaces the manager of an insolvent firm to devise and organize a liquidation or reorganization plan in the creditors' interest. In the course of the process, the insolvency administrator presents the most favourable option from his perspective, and the creditors choose to accept or reject this plan. Conflicts of interest arise because the insolvency administrator, as the better-informed party, considers in his proposal liability risks and reputational issues that are beyond the creditors' scope. We model this conflict as a Bayesian game and find that, under those compensation schemes typically used in real-world regulations, optimal creditor satisfaction and efficient decisions concerning the economic future of the insolvent firm will never be achieved simultaneously.
Keywords: 650; Bankruptcy; Insolvency administrator; Creditor; Incentives; Compensation